The Role of the Binkamsa Unit in Preventing the Crime of Theft with Aggravated Circumstances in North Lampung Police Area - Nabila Azizah Adama (Police Studies Review, 2021)
This research is motivated by the high number of criminal acts of theft with weights in North Lampung Regency. In accordance with Article 13 of Law Number 2 of 2002, it describes the main tasks to overcome threats, challenges, disturbances, and obstacles. Therefore, a research was carried out which aims to find out the general description of the crime of stealing in North Lampung Regency, analyze the role of the Binkamsa unit and determine the factors that affect the implementation of the task. The theory used is Management Theory, Communication Theory and Criminology Theory. The concepts used are the concept of binkamsa and the concept of roles which will be discussed later in the discussion of research results. The research method uses a qualitative approach whose results are strengthened by the findings, observations, document studies, and interviews with information sources. The techniques used for data analysis include data reduction, data presentation, and drawing conclusions. The results of the study found that theft with weighting was dominated because of economic problems and heterogeneous society. In the implementation of prevention there are still many shortcomings such as the lack of number and readiness of members, steep terrain and supervision and control. While the influencing factors such as humans, money, materials, machines, methods, and markets. Based on the results of the study, the researchers suggested that the leadership instruct members to carry out education and training, carry out regular analysis and evaluation, coordinate with the local government to provide skills training to prevent the crime of theft with weights at the North Lampung Police.